Provision and Implementation of Inclusive Education in Early Childhood Centers: A Comparative Case Study of Two Semarang-Based Institutions - Khotimah, Nur; Sutarto, Joko; Diana (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2023)
The present research aims to investigate and describe the provision of inclusive education services in early childhood education institutions, focusing on TK Hj. Isriati Baiturrahman 2 and PAUD Lab School UNNES in Semarang, Indonesia. Utilizing a qualitative descriptive case study approach, the study comprehensively examined various aspects, including curriculum, student demographics, educator training, infrastructure, and financing. Key findings indicate the utilization of a collaboratively developed "Merdeka Curriculum" aimed at holistic child development. Both schools have incorporated a specialized student selection process to identify and accommodate special needs students. Educators are rigorously trained in inclusive education methods and continuously monitored for program effectiveness. Infrastructure and funding support are pivotal for the actualization of inclusive practices. These findings have profound implications for practice and policy in inclusive education, reaffirming the necessity for inclusive school management and stakeholder involvement. However, the study is constrained by its localized focus and calls for further research to broaden its generalizability and investigate the long-term impacts of these programs.